The Effect of Audit Opinions, Liquidity and Leverage on the Timeliness of Financial Report Submission - Manuela, Vieri Leonardo; Marsyaf, Marsyaf; Bintara, Rista; Putra, Yananto Mihadi (Pelita : Jurnal Penelitian, Terapan dan Aplikatif, 2024)
The need for financial information presented in financial statements is very important for stakeholders in assessing the performance of a company. Especially in decision-making considerations. So that the fairness and timeliness of financial statement disclosure are important. This study aims to empirically test the factors that influence the timeliness of financial statement submission based on audit opinion, profitability level and company leverage level. This study uses quantitative research with secondary data. The sample in this study was a real estate and property industry sector company listed on the Indonesia Stock Exchange (IDX) in 2020 - 2022 and the company's official website. Sampling was carried out using the purposive sampling method, with several predetermined criteria, the number of samples was 90 real estate and property industry sector companies. And the results of this study indicate that audit opinion has a significant effect on the timeliness of earnings management, liquidity does not have a significant effect on the timeliness of financial statement submission, leverage does not have a significant effect on the timeliness of the company's financial statement submission.